EKSISTENSI PERS ISLAM DALAM DINAMIKA INDONESIA DI ERA MODERN - Ahmad Irfan Ilhami (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2018)
This study aims to examine the potential of the Islamic press in Indonesia in the modern era. The occurrence of media competition has caused the Islamic press in Indonesia to experience something that is dilemmatic. Starting from group interference which gave birth to the growth of the liberal Islamic press. Until the lack of Islamic mass media that carries the themes of tolerance and civilization in Islamic studies. The research method uses a library approach using techniques to analyze the contents of Islamic media. The validity of the data uses perseverance techniques and the rigorous preparation of relevant Islamic media news content. The results of the study found that da’wah media were able to reach all aspects, both children, adolescents, and parents. There is the power of the Islamic press which is under the unity of Muslims so that the Islamic press still exists in the modern era. The recent decline in the Islamic press is due to the inconsistency of the Islamic press in carrying out relevant themes for Islamic preaching positively. So that the Islamic press seems more trapped against market needs and tends to be more liberal. Even though the Islamic press should have its activeness in consuming media that has Islamic nuances, besides that innovation is also needed to develop the Islamic press with various methods, especially those relating to Islamic principles and values that promote tolerance and peace.Keywords: Existence, Islamic Press, Modern